Chemical and microbiological attributes of sandy soil fertilized with crushed green coconut shell - Barbosa de Paiva, Aparecida (Revista Ciência Agronômica, 2021)
The objective of this work was to evaluate the chemical composition of crushed green coconut shell and its effects on soil attributes. The treatments consisted of areas that received the residue and presented differences in the reaction time with the soil: 1 (T1); 12 (T2); 36 (T3) and 72 months (T4) and another area, in which the residue was not applied (T5). Samples of residues remaining on the soil surface were collected to evaluate the chemical composition and soils for chemical analysis, microbial activity, and arbuscular mycorrhizal fungi. Nutrients and sodium concentrations remained the same over time, providing, in order of magnitude, the contribution of organic C > K > N > Ca > Mg > Na > P > S > Fe > Mn > Zn > Cu to the soil. Over the periods evaluated, there were increases in the availability of elements, such as N, P, K and Na, and increases in the sum of base and cation exchange capacity of the soil. During the treatment with the longest period evaluated, there were increases in microbial biomass activity, measured by edaphic respiration and by metabolic and mineralization quotients. As time progressed, there were variations in communities of arbuscular mycorrhizal fungi, but this did not affect the diversity of fungal species. The most prevalent spore morphotypes belonged to Acaulospora laevis, A. scrobiculata and Claroideoglomus etunicatum. The application of 100 t ha-1 of crushed green coconut shell promotes changes in the chemical and microbiological soil attributes, especially in the fi rst months of the application of the residue. Reapplying residue 36 months after the fi rst application is recommended.